The Book of Genesis : A Biography - Hendel, Ronald S. (Book collections on Project MUSE., 2013)
During its 2,500-year life, the book of Genesis has been the keystone to almost every important claim about reality, humanity, and God in Judaism and Christianity. And it continues to play a central role in debates about science, politics, and human rights. With clarity and skill, acclaimed biblical scholar Ronald Hendel provides a panoramic history of this iconic book, exploring its impact on Western religion, philosophy, science, politics, literature, and more. Hendel traces how Genesis has shaped views of reality, and how changing views of reality have shaped interpretations of Ge.